Recombinant characterization and pathogenicity of a novel L1C RFLP-1-4-4 variant of porcine reproductive and respiratory syndrome virus in China - Xinyi Huang; Guoqing Liu; Tong Chang; Yongbo Yang; Tao Wang; Dasong Xia; Xinyu Qi; Xulong Zhu; Ziyi Wei; Xiaoxiao Tian; Haiwei Wang; Zhijun Tian; et al. (Veterinary Research)
Abstract Porcine reproductive and respiratory syndrome (PRRS) is one of the most significant diseases affecting the pig industry worldwide and is caused by the PRRS virus (PRRSV), which has complex genetic variation due to frequent mutations, indels, and recombination. The emergence of PRRSV L1C.5 in 2020 in the United States has raised worldwide concerns about PRRSV with the RFLP 1-4-4 pattern and lineage 1C. However, studies on the pathogenic characteristics, epidemiological distribution, and effectiveness of vaccines against PRRSV with L1C and RFLP1-4-4 pattern in China are still insufficient. In this study, a novel recombinant variant of PRRSV with RFLP 1-4-4 and lineage 1C features, different from L1C.5 in the United States, was isolated in China in 2021. In pathogenicity experiments in specific pathogen-free piglets or farm piglets, 60–100% of artificially infected experimental piglets died with high fever and respiratory symptoms. Inflammatory cytokine and chemokine levels were upregulated in infected piglets. A commercially modified live vaccine against highly pathogenic PRRSV did not provide effective protection when the vaccinated piglets were challenged with the novel L1C-1-4-4 variant. Therefore, this strain merits special attention when devising control and vaccine strategies. These findings suggest that extensive joint surveillance is urgently needed and that vaccine strategies should be updated to prevent the disease from spreading further.